IMPLEMENTASI PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM PADA MADRASAH TINGKAT DASAR DI KABUPATEN PASURUAN - Amang Fathurrohman; Mohammad Yusuf Wijaya; Endang Tyasmaning Tyasmaning; Hufron; Alfian Adi Saputra Saputra; Muhammad Holimi; Priatmojo Suryo Kuncoro; Fatmah K (Universitas Yudharta Pasuruan, 2020)
Islamic Cultural History Lessons have been studied at Madrasah Ibtidaiyah (MI) and Madrasah Tsanawiyah (MTs) in Indonesia. Using a qualitative method, which was sourced from 15 MI and MTs institutions taken randomly in 4 sub-districts in Pasuruan Regency. The results of this study indicate that many Islamic Cultural History Lessons Teachers still use lecture and discussion methods. Media often used are books and student worksheets. Teachers' problems in teaching media and learning facilities are limited, especially the availability of LCDs and access to Islamic History videos that are relevant to the subject matter. The learning process that relies heavily on the lecture method has implications for students who are bored and have difficulty understanding Islamic Cultural History subject matter. The solutions used include reviewing it repeatedly, providing motivation and innovating learning about Islamic Cultural History